2014
DOI: 10.1111/pce.12270
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin modulates proteomic, transcriptomic and growth responses to temperature shocks in Arabidopsis

Abstract: As sessile organisms, plants must sense environmental conditions and adjust their growth and development processes accordingly, through adaptive responses regulated by various internal factors, including hormones. A key environmental factor is temperature, but temperature-sensing mechanisms are not fully understood despite intense research. We investigated proteomic responses to temperature shocks (15 min cold or heat treatments) with and without exogenous applications of cytokinin in Arabidopsis. Image and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 87 publications
(158 reference statements)
3
25
0
Order By: Relevance
“…A rapid proteomic heat-shock response that could be mimicked to some extent by cytokinin treatment at standard temperature has also been reported [136], indicating that cytokinin may play a role in temperature perception. Moreover, the accumulation of cytokinin has been observed in Pinus radiata under prolonged heat stress and in recovered plants [137,138].…”
Section: Temperature and Cytokininmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid proteomic heat-shock response that could be mimicked to some extent by cytokinin treatment at standard temperature has also been reported [136], indicating that cytokinin may play a role in temperature perception. Moreover, the accumulation of cytokinin has been observed in Pinus radiata under prolonged heat stress and in recovered plants [137,138].…”
Section: Temperature and Cytokininmentioning
confidence: 99%
“…Accordingly, transgenic lines with inactivated components of cytokinin signalling pathways or reductions in pools of active cytokinin have displayed increased tolerance to high temperatures [141,142]. Further, analyses of temperature-induced hypocotyl growth in cytokinin-deficient transgenic plants and cytokinin receptor ahk double mutants have shown that impairment of the cytokinin pathway strongly inhibits growth at high temperatures [136]. This indicates that cytokinin could serve as a signal for thermomorphogenesis.…”
Section: Temperature and Cytokininmentioning
confidence: 99%
“…In the case of heat stress, CK effect on stomata opening followed by stimulation of leaf transpiration was found to be crucial at the early phase of the stress response (Mackova et al, 2013;Dobra et al, 2015;Skalak et al, 2016). Further, a large number of heat stress affected genes are CK-responsive (Cerny et al, 2014). CKs stimulate the antioxidant system upon heat stress .…”
Section: Introductionmentioning
confidence: 99%
“…may interfere with CK pathways involved in modulation of low and high temperature shocks [80,107], or directly with temperature-related perception and transduction [101].…”
Section: According To Arabidopsismentioning
confidence: 99%